Divergent Associations Between Serum Androgens and Ovarian Reserve Markers Revealed in Patients With Polycystic Ovary Syndrome - Li, Youran; Zhai, Yanhong; Li, Lin; Lu, Yifan; Su, Shaofei; Liu, Ying; Xu, Zhengwen; Xin, Mingwei; Zhang, Qiaoli; Cao, Zheng (Frontiers in Endocrinology, 2022)
Background: The role of excess androgen in ovarian reserve remains unclear in patients with polycystic ovary syndrome (PCOS). Our study highlights the associations of serum androgen levels and ovarian reserve markers in PCOS and non-PCOS women. Methods: Totally 584 menstrual abnormalities women of 20-45 years were retrospectively evaluated at the Beijing Obstetrics and Gynecology Hospital between January 2021 to October 2021. The enrolled patients were classified into two groups: the PCOS group (n=288) and the non-PCOS group (n=296) based on the Rotterdam consensus for PCOS diagnosis. The serum androgens, including testosterone (T), free testosterone (FT, calculated), bioavailable testosterone (Bio-T, calculated)，androstenedione (A2), dihydrotestosterone (DHT), dehydroepiandrosterone (DHEA), and dehydroepiandrosterone sulfate (DHEAS) were assessed with an in-house developed liquid chromatography tandem mass spectrometry (LC-MS/MS) method. The associations between the serum androgens and the hormone markers commonly used for evaluating ovarian reserve function, such as anti-mullerian hormone (AMH) and the ratio of luteinizing hormone (LH)/follicle stimulating hormone (FSH) were explored. Results: The serum T, FT, Bio-T, A2, DHT, DHEA, DHEAS, AMH and LH/FSH of the PCOS group were 51.7±23.2 ng/dL/mL, 8.5±5.0 pg/mL, 210.1±127.7 pg/mL, 1.9±0.8 ng/mL, 0.2±0.1 ng/mL, 6.4±4.2 ng/mL, 2431.0±1030.7 ng/mL, 6.7±3.8 ng/mL, and 1.8±1.4 respectively, which were significantly higher than those in the non-PCOS group (p<0.05). In the group of PCOS patients, T and A2 levels were positively associated with AMH in both multivariate linear regression analysis and Pearson’s correlation analysis. Similar but weaker associations were observed in the non-PCOS patients. In the PCOS patients with hyperandrogenemia (HA), the AMH level was significantly higher in the subjects with T increased than in the subjects with non-T androgen(s) increased (A2, DHT, DHEA or DHEAS). Conclusions: The serum androgen levels are positively associated with ovarian reserve markers in both of the PCOS and the non-PCOS patients in our study. In the PCOS group, the highest AMH level was observed in the subjects with the T elevation subgroup, suggesting that T is more closely related with the increase of AMH when compared with other androgens investigated.